Qualidade de vida dos usuários do transporte fluvial na Amazônia: acessibilidade e políticas públicas - COUTO, Mayra Hermínia Simões Hamad Farias do (Universidade Federal do Pará, 2017)
The river transport is the main form of displacement of traditional communities in the Amazon, and responsible for the quality of life and survival of riparian. The research aimed to describe how public policy and accessibility not carry river in the Amazon. The accessibility was assessed river Passenger Terminal In the cities of Santarém and Oriximiná and choose was made for the representativeness of the sample with exclusive transportation for population and they transport cargo. It was evaluated as Public Policy through the Political positioning in creation of new ports law using as shorthand notes. It was observed that the terminals in the Amazon not have an accessibility planned for national standards defined for the National Agency of Waterway Transportation (ANTAQ) and the Brazilian Association of Technical Standards (ABNT). As shorthand notes had largest placements in discussion as bid as areas port and contract maintenance time focusing greater cargo transportation areas and responsible amendment for the local assessment in the Amazon in order to generate as future Public Policy no had positioning parliamentary Amazon. By analyzing the quality of life addressing Infrastructure and how generated policies to river transport user Amazonian were observed there is little accessibility and how Public Policy in sector aim to transport cargo to the detriment of users and have little regional representation, not a national struggle political, negatively impacting the quality of life of inland waterway transport in the Amazon user, however no shortage of river transport studies, as research increase necessary being no paragraph sector future Public Policy planning that they encourage the accessibility in the Amazon.